Service Speed, Staff Courtesy, and Customer Satisfaction in Supermarkets in Awka Metropolis: The Mediating Role of Perceived Service Quality (Nigerian Journal of Cooperative Economics and Management, 2026)
This study examined the relationship between service speed, staff courtesy, and customer satisfaction among supermarket customers in Awka Metropolis, with perceived service quality serving as a mediating variable. A correlational survey design was adopted. Data were collected from 357 customers drawn from selected supermarkets in Awka Metropolis. Four types of structured questionnaires were employed in the data gathering process; namely Service Speed Questionnaire (SSQ), Staff Courtesy Questionnaire (SCQ), Perceived Service Quality Questionnaire (PSQQ) and Customer Satisfaction Questionnaire (CSQ). All the instruments used were validated through the marketing lecturers, while reliability was established through Cronbach’s alpha. Data were gathered from the customers in the supermarkets in Awka Metropolis. Out of 384 copies of the questionnaire distributed, 357 were correctly filled and used for data analysis. The analysis of the research questions one and two involved Pearson product-moment correlation, while multiple regression analysis was used for research question three. The findings revealed that there was a positive and significant relationship between service speed and customer satisfaction. There was also a positive and significant relationship between staff courtesy and customer satisfaction. Further to this, perceived service quality was found to mediate the aforementioned relationships. Service speed (r = 0.612, p < 0.05) and staff courtesy (r = 0.674, p < 0.05) significantly influenced customer satisfaction. The study concludes that customers would be more satisfied when services at supermarkets were fast, employees were polite, and the entire service process was reliable and satisfactory. It was proposed that the managers of supermarkets should enhance checkout speed, educate employees on how to be polite towards customers, supervise the service delivery process, and develop proper feedback mechanisms for customers.
Keywords: Service Speed; Staff Courtesy; Customer Satisfaction; Perceived Service Quality; Supermarkets